Capillary refill time paradoxically decreases in a blood loss shock model - Hugo Gustavsson; Frida Meyer; Sara Fahlander; Birgitta Ölwegård; Hanna Jonasson; Rani Toll; Joakim Henricson; Daniel Wilhelms (Intensive Care Medicine Experimental)
Abstract Background This study aimed to investigate whether changes in capillary refill (CR) time precede macrovascular signs of deterioration in a human model of blood loss shock. The study was conducted at the Department of Emergency Medicine in Linköping, Sweden, and involved 42 healthy volunteers aged 18–45. Participants were randomized into two provocations of applied lower body negative pressure (LBNP): a stepwise escalation protocol and a direct application protocol, to simulate gradual and acute blood loss. The main outcome measure was CR time. Systolic, diastolic, and mean arterial pressures, heart rate, cardiac output, and systemic vascular resistance were measured continuously. CR time was assessed on the finger pulp using a standardized pressure and measured with a polarized reflectance imaging system. Results The provocation elicited pre-syncope reactions and clear decrease in blood pressure for all participants, yet two-thirds of the participants in both protocols reacted with shorter CR times at maximum provocation, and the overall median CR time decreased by 0.2 s (Wilcoxon W = − 395.0, range: − 6.3 to 3.2, IQR − 1.3 to 0.1, P = 0.0070). Participants with shorter CR times exhibited comparatively greater increases in systemic vascular resistance and a more pronounced decrease in cardiac output. Conclusions Our findings reveal that finger CR time paradoxically decreases in a majority of healthy volunteers in a lower body negative pressure model of blood loss, challenging traditional assumptions about the CR test’s reliability as a shock indicator in its present interpretation.